TAKSONOMI MAKANAN DALAM BAHASA INGGRIS DAN BAHASA BATAK KARO: SUATU ANALISIS KONTRASTIF - BR PERANGIN-ANGIN, ASTRI THERESIA; PAMANTUNG, RINA P.; LOTULUNG, DONALD RINGGO (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACT This research entitled is ?Taxonomy of Food in English and Batak Karo Language: A Contrastive Analysis?. The objectives of this research are to identify, classify, analyze, and contrast the kinds and categories of food in English and Batak Karo language. In this research, the writer uses descriptive method. The writer read some books about taxonomy of food to find the theory. The data of food in English were collected from thesis, book, and article, while in Batak Karo language were taken from direct interview to some informants and also by taking pictures of the foods in some traditional markets and in Batak Karo traditional event called Kerja Tahun. The data about foods in English and Batak Karo language that have been collected then identified, classified, and analyzed by using the theory of Frisch in Hickerson. Then, the data of both languages were contrasted by using Lado?s theory. The results of this research showed that in English and Batak Karo language, there are no differences in the food categories because both have the same category, namely solid food and drinks. The differences found are English has four kinds of solid food, such as meat and fish or seafood, vegetables, breads, and fruits, but Batak Karo language has five kinds of solid food, such as meat and fish or seafood, vegetables,breads, fruits, and rice. Alcoholic drinks in English are found in two kinds, namely low and high alcoholic content, while in the Batak Karo language there is only one kind of alcoholic drinks found, namely tuak. Non-alcoholic drinks in English are found in five kinds, namely mineral water, refreshing drinks, tall drinks, stimulant, and nourishing, while in Batak Karo language there are nine of non-alcoholic drinks found, namely teh putih, teh susu, teh tawar, teh susu telor, teh manis, sirup markisah, jus martabe, kopi, and mumbang. Keywords: Taxonomy, Foods, English, Batak Karo Language, Contrastive Analysis